Why the Tobin tax can be stabilizing - Korkut Ertürk (Levy Economics Institute of Bard College, 2002)
This paper clarifies why a transaction tax of the type proposed by James Tobin can have a stabilizing influence in financial markets. It argues that such a tax is potentially stabilizing, not because it reduces the excessive volume of transactions, but because it can slow the speed with which market traders react to price changes. To the extent that a Tobin tax causes financial market traders to delay their decisions a few grains of sand in the wheels of international finance can indeed be stabilizing. Whether that is sufficient, or whether boulders-not just grains-are needed to prevent speculative attacks on currencies, is, however, a different matter.
Keywords: 330